Dose-staged Gamma Knife radiosurgery for meningiomas: A retrospective study in a single center - Gong, Xiu; Ding, Jianbo; Knisely, Jonathan P. S.; Wang, Enmin; Pan, Li; Wang, Binjiang; Zhang, Nan; Wu, Hanfeng; Dai, Jiazhong; Yu, Tonggang; Tang, Xuqun (Frontiers in Neurology, 2022)
Objective: This study aimed to study the efficiency and safety of a dose-staged Gamma Knife radiosurgery strategy for large meningiomas or meningiomas close to important nerve structures. Methods: This study evaluates the outcome of a prospectively accrued series of 71 consecutive patients with meningiomas treated with staged dose-fractionated Gamma Knife radiosurgery. The average peripheral dose for the first and second fraction was 9.0±0.9 Gy (8–12 Gy) and 8.6±0.7 Gy (range, 7–10 Gy), respectively. The interval between fractions was 6.1±1.9 months (range, 3–12 months). The median follow-up time was 36 months (12–96 months). Results: During the follow-up period after the second fraction, 97.2% achieved tumor control in our series. 2 patients exhibited local recurrence at 30 and 60 months after the second fraction, respectively. No treatment-related complications or new long-term neurological dysfunction was reported. MRIs observed slight or moderately increased peritumoral edema in six patients, but no specific neurological complaints are attributed to this finding. Conclusion: This study investigates the efficiency and safety of dose-staged Gamma Knife radiosurgery as an alternative option for meningiomas that were large in volume, adjacent to crucial structures, or in patients with contraindications to craniotomy.